k-NN improvement to data analysis - P. Mateva, Tonya; G. Ivanov, Ivan (International Journal of Engineering and Technology, 2019)
The problem to classify big data is an actual one the subject. There are multiple ways to classify data but the k Nearest Neighbors (k-NN) has become a popular tool for the data scientist. In this paper we examine several modifications of the k Nearest Neighbors algorithm that achieve better efficiency in terms of accuracy and CPU time when classifying test observations in comparison to the standard k Nearest Neighbors algorithm. To make the modifications faster than standard k-NN we use a special methodology which splits the input dataset into n folds and combine it with input data transformations. Each time we execute the process, one of the folds is saved as a test subset and the rest of the folds are applied for training. The process is executed n times. In the proposed methodology we are looking for the pair of subsets which produces the highest accuracy result.Â